Understanding the market of instant powder drink & future trend of GlaxoSmithKline Bangladesh Limited - Mahmud, Yestabshir (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.